Correlation the Link Between Students’ Self-Esteem and Reading Comprehension - Mudini, Siti; Nirwanto, Rahmadi; Widiastuty, Hesty (Journal Of Foreign Language Learning and Teaching, 2024)
This study explores the relationship between self-esteem and reading comprehension among male students at SMK Karsa Mulya. It addresses a notable phenomenon where male students often exhibit lower self-esteem compared to their female counterparts. This lower self-esteem can potentially affect various academic achievements, including reading comprehension. The aim of this research is to determine if there is a significant correlation between students' self-esteem and reading comprehension. Correlational research using quantitative methods. 53 students from Class XI for the academic year 2022/2023. SPSS 26 with the product-moment correlation method. The correlation coefficient (r) between self-esteem and reading comprehension was found to be 0.811. The significance level (p-value) was 0.00, which is less than the alpha level of 0.05. The (r table) for a sample of 53 at the 0.05 significance level is 0.279. The calculated correlation coefficient (0.811) exceeds the critical value (0.279) and the p-value (0.00) is below 0.05, the null hypothesis (Ho) is rejected in favor of the alternative hypothesis (Ha). The results indicate a strong positive correlation between self-esteem and reading comprehension among the male students studied. This suggests that higher self-esteem is associated with better reading comprehension skills. Improving students' self-esteem could potentially enhance their reading comprehension.